2008
DOI: 10.3748/wjg.14.2534
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of sister chromatid exchange frequencies in gastric cancer and chronic atrophic gastritis patients with and without H pylori infection

Abstract: AIM:To determine, by counting sister chromatid exchange (SCE) frequencies, whether genetic impairment and DNA damage have an effect on the pathogenesis of gastric cancer (GC). METHODS:Analysis of SCE is a cytogenetic technique used to show DNA damage as a result of an exchange of DNA fragments between sister chromatids. We analyzed SCE frequency in 24 patients with GC, 26 patients with chronic atrophic gastritis (CAG), and 15 normal controls. The presence of H pylori was confirmed by urease test, toluidine-blu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
(53 reference statements)
1
8
0
Order By: Relevance
“…Breast cancer patients also showed an increased frequency of SCE in a couple of previous studies, and this increased SCE had clinical and genetic significances (Roy et al, 2000;Aristei et al, 2009). Increased SCE was also found in gastric cancer and an H.pylori dependent increase has also suggested (Park and Kim, 1999;Karaman et al, 2008). Base on previous results, we investigated the SCE frequency in 69 gastric cancer patients.…”
Section: Discussionmentioning
confidence: 68%
“…Breast cancer patients also showed an increased frequency of SCE in a couple of previous studies, and this increased SCE had clinical and genetic significances (Roy et al, 2000;Aristei et al, 2009). Increased SCE was also found in gastric cancer and an H.pylori dependent increase has also suggested (Park and Kim, 1999;Karaman et al, 2008). Base on previous results, we investigated the SCE frequency in 69 gastric cancer patients.…”
Section: Discussionmentioning
confidence: 68%
“…They are considered as a more sensitive method than chromosome aberrations or micronuclei, since induced DNA damage can be demonstrated by the formation of SCEs even at low concentrations of genotoxic agents (Mourelatos et al, 1983;Mourelatos 1996). It has been found that SCEs frequency is increased in cancer patients' lymphocytes suffering from many kinds of cancer such as breast cancer, uterine cervix, ovarian, prostate and gastric cancer (Zhou, 1985;Dhillon et al, 1995;Dhar et al, 1996;Dhillon & Dhillon, 1998;Roy et al, 2000;Özturk et al, 2005;Cefle et al, 2006;Karaman et al, 2008;Aristei et al, 2009). MMC is a well known genotoxic agent which increases SCEs frequency in a wide range of cells and is widely used in order to measure chromosome fragility (Digkas et al, 2010 a ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, gastric cancer patients show higher levels of SCEs in their lymphocytes (Zhou, 1985;Karaman et al, 2008;Zhou et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…There were observations, which lead to the conclusion that substances that enhance the creation of chromatid exchanges, act as mutagens and carginogens and they multiplied the main interest around creating an exchange [14,15]. SCE in peripheral lymphocytes has been widely used to evaluate exposure to mutagens and carcinogens [16,17]. It is a very sensitive and relatively quick process that can be used in tumor or normal cells, to in vitro and in vivo experiments [18].…”
mentioning
confidence: 99%